Comparative growth analysis of Candida dubliniensis and Candida albicans in vitro and in selected infection models - Stokes, Cheryl (Trinity College (Dublin, Ireland). School of Dental Science, 2006)
Candida dubliniensis is the species most closely related to C. albicans and is primarily associated with colonisation and oral candidiasis in Human Immunodeficiency Virus (HlV)-infected individuals and AIDS patients. Despite the similarities between the two, epidemiological data and results from in vivo infection models indicate that C. albicans is significantly more pathogenic than C. dubliniensis. The purpose of this study was to investigate if differences in growth might explain this apparent difference in the ability of C. albicans and C. dubliniensis to cause disease. Candida dubliniensis strains demonstrated a significantly slower growth rate than C. albicans strains in both Sabouraud liquid broth, modified antibiotic medium 13 (SDB) and yeast nitrogen base medium (YNB). Kirkpatrick et ai, have previously reported that C. albicans has the capacity to out-compete C. dubliniensis when grown in co-culture, and C dubliniensis was only present in two out of eleven pairings after 96 h of growth in SDB medium using CHROMagar Candida medium to differentiate between the two species (Kirkpatrick et ai, 2000). In the present study CHROMagar Candida medium was deemed an inefficient means of discriminating between the species, therefore in order to facilitate efficient discrimination, strains were tagged with a molecular cassette containing genes encoding mycophenolic acid resistance (MPA R) and green fluorescent protein (GFP). The two species were examined in co-culture in both SDB and YNB and differentiation was performed on MPA-containing and drug-free media. Candida dubliniensis strains were always found to be present in significantly lower amounts than C. albicans strains, which is most likely due to their slower growth rate.
Keywords: Dental Science, Ph.D.; Ph.D. Trinity College Dublin